2008
DOI: 10.1136/bjsm.2008.047407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sports activity in athletes with bicuspid aortic valve and mild aortic regurgitation

Abstract: Left ventricular dimensions in competitive BAV athletes remain within the normal range. There is, however, a significant progressive increase in the BAV group compared with the TAV group. These results are in agreement with data obtained in previous studies on the non-athletic BAV population. Sports activity does not have an additional effect on cardiac morphology in athletes with asymptomatic BAV associated with mild regurgitation, for at least 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 28 publications
1
29
1
1
Order By: Relevance
“…Aortic root was measured at the aortic valve annulus in 15 studies 7,[18][19][20][23][24][25]27,28,30,31,34,36,38,39 and at the sinuses of Valsalva in 12 studies. 7,[21][22][23][24]26,28,29,32,33,35,37 (Tables 1 and 2). In the 13 studies that directly compared athletes with controls, there were variations in the degree of matching; 11 studies matched for age, and 3 studies explicitly stated that they matched for body size.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aortic root was measured at the aortic valve annulus in 15 studies 7,[18][19][20][23][24][25]27,28,30,31,34,36,38,39 and at the sinuses of Valsalva in 12 studies. 7,[21][22][23][24]26,28,29,32,33,35,37 (Tables 1 and 2). In the 13 studies that directly compared athletes with controls, there were variations in the degree of matching; 11 studies matched for age, and 3 studies explicitly stated that they matched for body size.…”
Section: Resultsmentioning
confidence: 99%
“…28 Yearly echocardiograms performed in 88 athletes with BAV for 5 years demonstrated that the proximal ascending aorta increased by 0.98 mm/y. 28 This rate of increases is comparable to that observed in nonathletes with BAV, which ranges among studies from ≈0.2 to 1.9 mm/y.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcomes data on ascending thoracic aortic aneurysms and exercise are also lacking. In the bicuspid aortic valve (BAV) population which is associated with progressive aortic enlargement, a study by Galanti et al 34 found that over a 5-year period, the rate of aortic growth for athletes was no different than for the sedentary, non-athletic BAV population. However, the genetics associated with BAV remains elusive and the pathogenesis may be very different from Marfan syndrome and related conditions.…”
Section: Lack Of Outcomes Datamentioning
confidence: 99%
“…It has been suggested in previous studies that these “normal” alterations have implications for mitral and tricuspid valve function if annular dilatation causes incomplete closure of the valve leaflets 1214. A varying prevalence of valvular regurgitation has been reported in athletes 1417…”
mentioning
confidence: 99%